PENGARUH MOTIVASI KERJA GURU TERHADAP KINERJA GURU AKUNTANSI SMK DI KOTA MADIUN - Titin Eka Ardiana (ITB AAS INDONESIA, 2017)
This study aims to determine the effect of motivation on teacher performance accounting work. This study uses a correlational study approach with samples taken from the accounting teacher in SMK Madiun incluster random sampling as much as 97 people. The variables of this study consists of one independent variables, namely: work motivation (X) and one dependent variable is: accounting teacher performance (Y). The data was collected using a structured question naire covered. Results of data collection were then analyze dusing regression analysis technique simple and multiple regression using SPSS version 20. The results show that a positive effect on work motivation on teacher performance accounting with a contribution of 80,6%, remaining at 19,4% accounting teacher performance is determined by factors other than research.Keywords : motivation and teacher performance accounting